PENGARUH SPIRITUAL LEADERSHIP, BUDAYA ORGANISASI DAN PERILAKU KERJA TERHADAP KINERJA PEGAWAI PADA RUMAH TAHANAN NEGARA KELAS IIB UNAAHA - Indra Frediansyah; Aidin Hudani Awasinombu; Samdin Samdin (Pascasarjana Universitas Halu Oleo, 2020)
The purpose of this study was to determine the effect; 1) the influence of spiritual leadership, organizational culture and work behavior simultaneously on employee performance. 2.) the influence of spiritual leadership, on employee performance. 3.) the influence of organizational culture on employee performance and 4) the influence of work behavior on employee performance. the research method is to use quantitative research. the data used are secondary and primary data. data analysis usingspss software version 20. the sampling technique uses saturated sample amounted to 51 employees at class iib unaaha state prison. the results showed that; 1) spiritual leadership, organizational culture and work behavior simultaneously have a positive and significant impact on employee performance. 2)spiritual leadershippositive and significant effect on employee performance. 3)organizational culture has a positive and significant effect on employee performance. 4) work behavior has a positive and significant effect on employee performance.